Hubungan Prilaku Pemberian MP-ASI dan Kejadian Diare dengan Status Gizi Bayi Usia 6-11 Bulan Di Puskesmas Simpang Kawat Kota Jambi - Indah Eptika; Djayusmantoko Djayusmantoko; Merita Merita (Universitas Baiturrahim, 2019)
Provision of complementary feeding that is too early has an impact on the incidence of diarrhea. The purpose of this study was to determine the relationship between the behavior of giving complementary feeding and the incidence of diarrhea with the nutritional status of 6-11 month-old infants at the Primary Health Center of Simpang Kawat in Jambi City, 2019 years. This study used a cross sectional study design. The research sample is infants aged 6-11 months as many as 75 infants with accidental sampling technique. Collecting data through questionnaires and interviews with mothers and anthropometric measurements (Weight/Aged). Data was analyzed using univariate and bivariate test (chi-square). The result showed that the giving of complementary feeding was good (52.0%), and the provision of complementary feeding was not good (48.0%). The incidence of diarrhea was as much as 40.0% and not diarrhea as much as 60.0%. Good nutritional status (98.7%) and poor nutritional status (1.3%). The chi-square test analysis showed that there is no correlation between the provision of complementary feeding with nutritional status in infants aged 6-11 months in (p-value=1,000) and there is no relationship between the incidence of diarrhea with nutritional status in infants 6-11 months (p-value=0,400). It is recommended to heatlh officers to provide education to mothers related to giving complementary feeding and preventing incidence of diarrhea so as not to have an impact on the nutritional status of infants.